2007
DOI: 10.1016/j.bbrc.2007.10.049
|View full text |Cite
|
Sign up to set email alerts
|

A NPxY-independent β5 integrin activation signal regulates phagocytosis of apoptotic cells

Abstract: Integrin receptors are heterodimeric trans-membrane receptors with critical functions in cell adhesion and migration, cell cycle progression, differentiation, apoptosis, and phagocytosis of apoptotic cells. Integrins are activated by intracellular signaling that alter the binding affinity for extracellular ligands, so-called inside to outside signaling. A common element for integrin activation involves binding of the cytoskeletal protein talin, via its FERM domain, to a highly conserved NPxY motif in the beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…However, α V β 5 (35) and INA-1-PAT-3 (10) seem to reside at the point furthest upstream in the pathway CED-2/CED-5/CED-12/ CED-10, not CED-6/CED-7/CED-10. In addition, the NPxY motif contained in β 5 integrin was shown to be dispensable for α V β 5 -mediated phagocytosis (36). In contrast, mammalian stabilin-2, a phosphatidylserinebinding engulfment receptor, uses its NPxY motif to recruit the mammalian orthologue of CED-6 (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, α V β 5 (35) and INA-1-PAT-3 (10) seem to reside at the point furthest upstream in the pathway CED-2/CED-5/CED-12/ CED-10, not CED-6/CED-7/CED-10. In addition, the NPxY motif contained in β 5 integrin was shown to be dispensable for α V β 5 -mediated phagocytosis (36). In contrast, mammalian stabilin-2, a phosphatidylserinebinding engulfment receptor, uses its NPxY motif to recruit the mammalian orthologue of CED-6 (37).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular region of ␤ subunits contains the amino acid sequence NPXY that is bound by the cytoskeleton protein talin (46), and this binding is believed essential for the activation of integrin. It is therefore worth knowing whether talin interacts with signal mediators of the engulfment pathways, although there is a report that the activation of integrin ␤ 5 in the phagocytosis of apoptotic cells occurs independent of the NPXY motif (47).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, upon stimulation with Gas6, Mer triggers an anti-inflammatory pathway involving PI3K/Akt/GSK3b signaling and NF-kB inhibition in immune cells (Alciato et al, 2010;Eken et al, 2010). In addition, Mer mediates the induction of phosphorylation of cytoskeletal proteins p130cas and FAK, which have been previously implicated in apoptotic cell phagocytosis (Wu et al, 2005;Singh et al, 2007). Previously, our in vivo study found that blocking the interaction of Mer with its ligand using antiMer neutralizing antibody results in decreased LPS-induced Mer activation (given that full-length Mer protein expression is suppressed) as well as downstream signaling (Lee et al, 2012a).…”
Section: Tapi-0 Treatment Reduces Smer Production Andmentioning
confidence: 99%